Current Trends in Cancer Management - Streba, Liliana; Ionut Gheonea, Dan; Schenker, Michael (IntechOpen, 2019)
The field of cancer diagnosis, prognosis, and treatment is constantly advancing. From novel biomarkers to cutting-edge imaging solutions, changing chemotherapy protocols and novel immune-targeting agents, medical teams develop and test new ways to manage this ever-growing threat to the modern age. Imaging has been a reliable method for initial diagnosis and later surveillance of premalignant and cancerous lesions of the digestive tract. This book project aims to characterize the main diagnostic procedures and novel medical and surgical treatments, as well as provide an updated view on current guidelines, premalignant lesions management, and minimally invasive curative techniques.